Comparative Perspectives on Precarious Employment Database (CPD) - Vosko, L; Vosko, Leah (Toronto, 2014)
The Comparative Perspectives on Precarious Employment Database (CPD) brings together a library of relevant sources in the field, unique user-friendly statistical tables, and a thesaurus of concepts – all related to research on precarious employment. Users can analyze multidimensional tables to explore and compare the contours of precarious employment in thirty-three countries, including Australia, Canada, the United States, twenty-seven European Union (EU) member countries and three non-EU member countries.
Keywords: Employment -- Security of employment; Employment -- Labour markets; Employment; Gender; Surveys and Survey Methodology -- Survey comparison; Surveys and Survey Methodology; Gender; Surveys and survey methodology; Gender; Surveys and Survey Methodology; Employment; Labour markets; Security of employment; Survey comparison; Surveys and Survey Methodology; Gender